Entrepreneurship Education Management In Realizing The Independence Of Boarding Schools In Langkat - Ahmad Zaki; Fachruddin Fachruddin; Sahkholid Nasution (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Every educational institution, including Islamic boarding schools, is facing challenges that arise along with the progress of the times, namely the modernization of education. Every educational institution is required to have a good management system, so that it is able to plan, organize, implement, control and evaluate its own educational institutions. Islamic boarding schools as educational institutions that have been synonymous with conventional management systems and do not keep up with the times, feel the need to make several changes in order to become independent institutions, especially from the aspect of economic independence. One alternative that can be chosen by institutions to achieve institutional independence is entrepreneurship education. Islamic boarding schools that implement entrepreneurship education are Darussaadah Islamic Boarding School Pangkalan Susu and Al-Habib Sei Lepan Islamic Boarding School. This study aims to analyze and find, 1). entrepreneurship education strategy in realizing the independence of Islamic boarding schools, 2). implementation of entrepreneurship education strategies in realizing the independence of Islamic boarding schools 3). implications of entrepreneurship education strategies in realizing the independence of Islamic boarding schools. This research uses a qualitative approach with a multi-site study type. The data collection technique uses in-depth interviews, participant observation and documentation. Data analysis used the Myles Huberman model of data reduction, data presentation, verification and drawing conclusions. Data is analyzed from single site and cross site data. Test the validity of the data through credibility, transferability, dependability and confirmability. The research results show 1). The entrepreneurship education strategy used is student engagement in each stage of entrepreneurial activity and designing meaningful learning, 2). the implementation of entrepreneurship education strategies at Islamic boarding schools uses peer tutorial, trial and error methods and students as entrepreneurship education mentors also use a prophetic approach, namely not basing entrepreneurial activities solely on obtaining financial benefits, but also for spiritual motives, 3). the implications of entrepreneurship education in Islamic boarding schools are increasing economic independence and institutional management as well as increasing the independence of students. The formal finding of this study is that entrepreneurship education is based on the development of aspects of entrepreneurial knowledge (knowledge), entrepreneurial skills (skills), attitudes (attitudes), and individual and environmental spirituality (spirituality).